Facile Preparation of Hydrophobic Aluminum Oxide Film via Sol-Gel Method - Fang, Changqing; Pu, Mengyuan; Zhou, Xing; Lei, Wanqing; Pei, Lu; Wang, Chenxi (Frontiers in Chemistry, 2018)
Hydrophobic aluminum oxide films (AOFs) are widely used in anti-oxidation and anti-corrosion applications. In preparing AOFs, complex and high temperature conditions are usually necessary. Here, we report aluminum nanowire structures with hydrophobic properties, prepared using a facile sol-gel method by magnetic stirrer and hydrothermal reaction. The electromagnetic force work has great influence on the structure of AOFs. The surface morphology and compositions of the AOFs were analyzed by scanning electron microscope (SEM), energy dispersive X-ray spec-trometers (EDS), X-ray diffraction (XRD), 3M peeling test and X-ray photoelectron spectroscopy (XPS). With the increase of water content in hydrothermal reaction, the hydrophobicity of AOFs proportional increased. Adding 10 ml deionized water leads to the formation of the upper nanowires and the lower nanohole with 129.3 ° water contact angle. Meanwhile, the AOF provide a good substrate for electroless deposition (ELD) of copper (Cu) to achieve a simple fabrication of metal conductor.